If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -5j = -94 Solving 6 + -5j = -94 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -5j = -94 + -6 Combine like terms: 6 + -6 = 0 0 + -5j = -94 + -6 -5j = -94 + -6 Combine like terms: -94 + -6 = -100 -5j = -100 Divide each side by '-5'. j = 20 Simplifying j = 20
| -0.5x+10=1.5x-5 | | -(5x+12)=12 | | -j+4k+jk-5jk+5j= | | 12x^2+5x-2x=0 | | .83+3j=-.67 | | 10y-4y= | | 20x-5=7+18x | | -8n+4(1+5n)=-6n+-14 | | s=4s-6 | | -0.9x+xy-0.8y+2y= | | 100x^2-4=0 | | 7=-56w | | c=38.34+0.50x | | 38.34=c+0.50x | | 3(y-2)=15-4y | | 74-3x=6x+23 | | 38.34=cx+0.50 | | C=24+35 | | 6+3n=4-5n | | 10+4q=12+3q | | 77-9y=23 | | x=38.34x+0.50 | | 15=-.6n | | 3x+5+3y+108=180 | | 4(x+5)=5(3x-7) | | 3*4-8=8 | | x+5=y-50 | | 8x-6=32 | | 3x+5+37+108=180 | | 15-x=5.2 | | 5b+40=20b+40 | | 8+m=9m-7 |